Phytochemical And Antibacterial Properties Of Ethanol Extract Of Syzygium Cumini Seed On Pathogenic Bacteria (Journal of Plant Disease Sciences, 2018)
Phytochemical investigation was carried out on the crude ethanol and aqueous extracts of Syzygium cumini . The antimicrobial activity of seed extract was tested against standard strains and clinical isolates of five bacteria using the agar well diffusion method. In Preliminary phytochemical analysis the presence of flavonoids, alkaloids, glycosides, steroids, phenols, saponins, terpenoid, cardiac glycosides and tannins were present in the extracts. The extracts showed inhibitory activity against pathogenic, gram negative bacteria viz, Pseudomonas aeruginosa and Escherichia coli, Proteus vulgaris and gram positive bacteria were Bacillus subtilis, and Staphylococcus aureus. The results showed that the ethanol extracts was more potent than the aqueous extracts.
Keywords: Syzygium cumini seed; Extracts; Phytochemical Screening; Antibacterial Activity